Politics and ethics in South Africa : a study in the identification and evaluation of political alternatives - Du Toit, A. B.(Andries Bernhardus),1931- (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1974.